Stress Tolerance and Contribution to Aroma Profile of Pichia kudriavzevii GAAS-JG-1 Isolated from Apricot Fermentation in Co-Fermentation of Sea Buckthorn Wine - Yuwen Mu; Yu’an Wang; Chaozhen Zeng (Microorganisms)
High-acidity fruit wines, such as sea buckthorn wine, are valued for their nutritional benefits but often suffer from excessive tartness and limited aroma complexity, which restrict their consumer acceptance. The application of non-Saccharomyces yeasts with acid tolerance and flavor-enhancing potential offers a promising strategy to address these challenges. In this study, a highly acid-tolerant yeast strain, Pichia kudriavzevii GAAS-JG-1, was isolated from a naturally fermented apricot system and systematically characterized in terms of its taxonomy, physiological properties, and fermentation potential. The experimental results demonstrated that Pichia kudriavzevii GAAS-JG-1 maintained robust growth activity (OD600 = 1.18 ± 0.09) even under extremely acidic conditions (pH 2.0). Furthermore, the strain exhibited a strong tolerance to high ethanol concentrations (16%), elevated sugar levels (350 g/L), and substantial sulfur dioxide exposure (500 mg/L). Optimal growth was observed at 35 °C (OD600 = 2.21 ± 0.02). When co-fermented with Saccharomyces cerevisiae in sea buckthorn wine, the ethyl acetate content increased significantly from 303.71 μg/L to 4453.12 μg/L, while the ethyl propionate levels rose from 5.18 μg/L to 87.75 μg/L. Notably, Pichia kudriavzevii GAAS-JG-1 also produced novel flavor compounds such as methyl acetate and ethyl 3-methylthiopropionate, which were absent in the single-strain fermentation. These findings highlight the potential of Pichia kudriavzevii GAAS-JG-1 as a valuable non-Saccharomyces yeast resource with promising applications in the fermentation of high-acidity specialty fruit wines.